ANALISA VARIASI UKURAN RUNNER SYSTEM DAN MELT TEMPERATURE TERHADAP FILL TIME, CONFIDENCE OF FILL DAN QUALITY PREDICTION - Mario Sariski Dwi Ellianto; Midarto Dwi Wibowo; Kadex Widhy Wirakusuma (Otopro)
The technology used in making plastic products is injection molding technology. In general, the products obtained are not of good quality, so simulations need to be carried out to determine the correct production process parameters. This research focuses on determining the effect of variations in runner system size and variations in melt temperature on the optimal fill time, confidence of fill, and quality prediction for tensile test specimen products. This research uses a simulation approach with the help of software. The simulation method is used to determine the characteristics of each variation in runner size and melt temperature. The type of runner layout used is a grid layout type, the runner system type is H balance, and the cross-section type is circle-shaped. Variations in runner size use runner diameters of 2 mm, 3 mm, and 4 mm. Variations in melt temperature use values of 190°C, 200°C, and 210°C. The simulations carried out include fill time analysis, confidence of fill analysis, and quality prediction analysis. Simulation results of fill time, confidence of fill and quality prediction at a runner diameter of 2 mm and melt temperature of 210°C yielded optimal values of 0.7524 s, 100% and 95.1%, respectively. These conditions ensured that the molten polymer remained in a fully flowable state until complete cavity filling was achieved, thereby minimizing the risk of defects and enhancing cycle time efficiency. An increase in runner size results in reduced flow resistance of the molten material, while the melt temperature remains within the process conditions recommended by the material manufacturer.